Jafar Khandan about Mirza Fatali Akhundov (Eurasian Journal of Philology Science and Education, 2015)
Artistic, scientific, philosophical thoughts of Akhundov researches in article named “Jafar Khandan about M.F. Akhundov”. J.Khandan tells thoughts about M.F. Akhundov’s heritage unsaid up to him, expresses Akhundov’s fight against backwardness of whole East World for his population to become educated and everything that he done for development of enlightenment there. He also brings into attention the role of revolutionary – democratic events of West and Russia in perfection of M.F. Akhundov as a philosophy who came to the literature with poetry, makes independence, humanism, patriotism, women’s freedom, nationality ideas in his thoughts to be known. He also mentions Akhundov’s endeavour opendefence and ground of materialist philosophy and atheism in public thought of Azerbaijan and mentions existence of idea leaders of democratic enlightenment in Azerbaijan fighting against religion, feudal patriarchal system and East despotism. Jafar Khandan emphasizes the importance of comprehensive deep study of creativity of Akhundov, and also reprinting of all its works in the Russian and Azerbaijani languages. Akhundov-avtor first realistic story «The Deceived Stars» in the Azerbaijani literature. Really, as the founder of the Azerbaijani realistic dramatic art and prose,and also the adherent of aesthetic-materialistic views to Mirza Akhundov is known by many compatriots.
Keywords: Jafar Khandan; Akhundov; fanatism; enlightenment